Dynamics of Land and Building Acquisition Tax Collection in West Lombok Regency: Challenges and Achievements - Baiq Isyana Rahmiyanti; Ahmad Amir Aziz; Baiq Ratna Mulhimmah (STKIP Taman Siswa Bima, 2025)
Land and Building Acquisition Fee (BPHTB) is an important component of Regional Original Income (PAD) which has a strategic role in supporting development in West Lombok Regency. This study aims to analyze the dynamics of BPHTB collection during the 2020–2023 period using a qualitative-descriptive approach through SWOT analysis. The results of the study show that although BPHTB revenues have increased significantly, its contribution to PAD still faces various challenges, such as the gap between targets and realization, low taxpayer compliance, and bureaucratic and supervisory problems. Factors such as property investment growth, fiscal policy, and information systems that have not been integrated also affect the effectiveness of tax collection. The proposed optimization strategies include digitalization of services, simplification of bureaucracy, improving the quality of regulations, and creating a conducive investment climate. With these steps, BPHTB is expected to become an effective fiscal instrument in strengthening regional fiscal capacity and accelerating development in West Lombok.